(untitled) (Jurnal Sustainable, 2023)
This research focuses on eliminating facilities and infrastructure in an institution or educational institution. This research uses qualitative methods with a literature approach. The study results show that Elimination is included in the infrastructure management process as a form of liberation of infrastructure facilities from accountability that has been imposed. This can be seen from 1) the definition of the Elimination of facilities and infrastructure, namely the Elimination of facilities and infrastructure is a procedure that tries to remove facilities and infrastructure from the inventory list; 2) the purpose of the Elimination of facilities and infrastructure, namely the purpose of the Elimination is to reduce the loss of institutions in the maintenance of goods or equipment, increase budget efficiency, provide freedom to institutions of security, guard, and accountability of goods, and reduce the burden of maintaining inventory; 3) conditions for the removal of facilities and infrastructure, namely the conditions for the removal of infrastructure facilities must be in a state of severe damage; 4) the mechanism for the Elimination of facilities and infrastructure, namely the elimination mechanism carried out by auctioning and destroying procedures; 5) procedures for the Elimination of facilities and infrastructure, i.e. The municipality has established procedures for the removal of educational facilities and infrastructure that must be followed to save money and vacate classrooms.